Near and generous? Gift propensity and chosen emotional distance - Kari H. Eika (University of Oslo, Department of Economics, 2011)
This experimental study asks whether generosity decreases emotional distance, a question pertinent to human service quality. Highly vulnerable service recipients may not enforce quality standards. Quality can then be viewed as an act of generosity, a gift from the provider to the recipient. For a human service provider that sympathizes with the recipient, delivering poor quality is psychologically costly. To reduce this cost she may increase emotional distance. Since human service quality presupposes social interaction and involvement, quality is reduced further. The mechanism - which can account for vicious and virtuous circles in the provision of quality - is explored in a binary dictator game where the recipient's pay-off is uncertain. The dictator decides whether to know the recipient's pay-off and how. Subjects are more eager to inquire about their recipient's pay-off when they themselves have been generous, and to do so by contacting the recipient when the recipient correctly perceives that action to be kind.
Keywords: C9; D03; D23; D64; I11; I21; 330; human services; emotional distance; cognitive dissonance; generosity; dictator game